Unraveling Academic Procrastination: The Roles of Self-Efficacy, Online Game Addiction, and Peer Conformity in University Students - Anis, Daffa Dania Nur; Murniasih, Farhanah (Journal An-Nafs: Kajian Penelitian Psikologi, 2025)
Many university students struggle with academic procrastination, with approximately 52% regularly delaying or neglecting academic responsibilities. This study employed a quantitative approach to examine how self-efficacy, online game addiction, and peer conformity jointly influence academic procrastination among university students. The sample comprised 214 students from a State Islamic University in Banten, aged 18–21, who engaged in online gaming for more than four hours daily. Data were collected using validated psychological scales, including the Procrastination Assessment Scale–Student (PASS), General Self-Efficacy Scale (GSE), Game Addiction Scale for Adolescents (GASA), and a peer conformity scale. Confirmatory Factor Analysis (CFA) and multiple regression analysis were used to assess construct validity and test hypotheses. The results revealed that the three predictor variables explained 19.0% of the variance in academic procrastination, but only the "problems" dimension of online game addiction showed a significant positive effect. Self-efficacy and peer conformity did not significantly predict procrastination. This study offers a novel contribution by integrating internal and external predictors into a single explanatory model and examining them within the culturally specific context of Muslim university students. The findings underscore the importance of addressing behavioral disruptions—especially problematic gaming—rather than relying solely on enhancing self-efficacy or modifying peer norms. These insights can inform targeted intervention programs to help students manage academic responsibilities more effectively and reduce maladaptive gaming habits.